Study on scatter radiation of low energy X-ray absorbed dose to water measurement - LU Pingzhou; WU Jinjie; LI Mengyu; QU Bingbing; SONG Fei; FAN Song; ZHOU Jianbin; ZHAO Rui (He jishu, 2022)
BackgroundLow energy X-rays are often used in superficial radiotherapy, its air kerma or absorbed dose to water is usually measured with a plane-parallel ionization chamber.PurposeThis study aims to investigate the response of the plane-parallel ionization chamber in the low energy X-ray calibration process and the scattering caused by the change of the radiation field.MethodsFirst of all, Monte Carlo simulation of four reference radiations (30 kV, 25 kV, 50 kV(b) and 50 kV(a)) was carried out in the low-energy X-ray standard radiation field. Then, two commonly used plane-parallel ionization chambers. i.e., PTW23344 and PTW23342, were calibrated and measured in air and phantom respectively by experiment, and the size of radiation field was changed by using different secondary apertures.ResultsThe readings of the two ionization chambers increase with the increase of the diameter of the radiation field, but the overall trend is gradually flattening. Ratios between chamber's readings in air and in phantom of the two ionization chambers decreases as the diameter of the radiation field decreases, and the overall trend gradually flattening. The average increase in the calibration coefficient of the absorbed dose to water in the radiation field of the PTW23344 ionization chamber in the range of 4.5 cm to 9 cm is 2.85 times that in the range of 9 cm to 13.5 cm whilst the average increase of the calibration coefficient of the absorbed dose to water in the range of 2.03 cm to 4.05 cm is 1.50 times that in the range of 4.05 cm to 6.08 cm in the radiation field.ConclusionsIt is necessary to make the radiation field completely cover the sensitive volume of the ionization chamber to achieve the condition of electron balance measurement, but not too large to cause too much scattering and damage.